Cost-effectiveness analysis of use of a polypill versus usual care or best practice for primary prevention in people at high risk of cardiovascular disease. - Sue Jowett; Pelham Barton; Andrea Roalfe; Kate Fletcher; F D Richard Hobbs; Richard J McManus; Jonathan Mant (PLoS ONE)
Background Clinical trials suggest that use of fixed-dose combination therapy ('polypills') can improve adherence to medication and control of risk factors of people at high risk of cardiovascular disease (CVD) compared to usual care, but cost-effectiveness is unknown. Objective To determine whether a polypill is cost-effective compared to usual care and optimal guideline-recommended treatment for primary prevention in people already on statins and/or blood pressure lowering therapy. Methods A Markov model was developed to perform a cost-utility analysis with a one year time cycle and a 10 year time horizon to compare the polypill with usual care and optimal implementation of NICE Guidelines, using patient level data from a retrospective cross-sectional study. The model was run for ten age (40 years+) and gender-specific sub-groups on treatment for raised CVD risk with no history of CVD. Published sources were used to estimate impact of different treatment strategies on risk of CVD events. Results A polypill strategy was potentially cost-effective compared to other strategies for most sub-groups ranging from dominance to up to £18,811 per QALY depending on patient sub-group. Optimal implementation of guidelines was most cost-effective for women aged 40-49 and men aged 75+. Results were sensitive to polypill cost, and if the annual cost was less than £150, this approach was cost-effective compared to the other strategies. Conclusions For most people already on treatment to modify CVD risk, a polypill strategy may be cost-effective compared with optimising treatment as per guidelines or their current care, as long as the polypill cost is sufficiently low.